2014
DOI: 10.4103/0019-5278.146887
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea and occupational accidents: Are oral appliances the solution?

Abstract: Background:Dental practitioners have a key role in the quality of life and prevention of occupational accidents of workers with Obstructive Sleep Apnea Syndrome (OSAS).Aim:The aim of this study was to review the impact of OSAS, the Continuous Positive Airway Pressure (CPAP) therapy, and the evidence regarding the use of oral appliances (OA) on the health and safety of workers.Materials and Methods:Searches were conducted in MEDLINE (PubMed), Lilacs and Sci ELO. Articles published from January 1980 to June 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 98 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…4,6 Research conducted on a group of Canadian drivers revealed that drivers suffering from OSA had a higher traffic accidents factor than healthy drivers during a 3 year period. 7 Other OSA symptoms are xerostomia, increased saliva secretion, change in sleep rituals and dyspnea. Daytime symptoms usually include headaches, irritability and stomach reflux.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Research conducted on a group of Canadian drivers revealed that drivers suffering from OSA had a higher traffic accidents factor than healthy drivers during a 3 year period. 7 Other OSA symptoms are xerostomia, increased saliva secretion, change in sleep rituals and dyspnea. Daytime symptoms usually include headaches, irritability and stomach reflux.…”
Section: Introductionmentioning
confidence: 99%